Language, childhood, mimesis – approaching childhood through the works of Giorgio Agamben and Walter Benjamin - Ilyés, Zalán György (Acta Cultura et Paedagogicae, 2026)
As the title of the paper suggest, in this study I will examine a conceptual constellation that can be complemented by other concepts (idea, voice, image, writing) in addition to those mentioned in the title. Following Walter Benjamin, one could even say that this constellation is in fact nothing other than the idea of childhood. There is no doubt that this approach to childhood leads us toward a concept of childhood that is quite far removed from our everyday conceptions of it. Yet, its significance lies precisely in the problem which I reconstruct in the opening of my paper and which we might briefly call the problem of the crisis of tradition. The author of this paper agrees with those interpreters who look in the figure of the child for elements of a “new barbarism” that can lead us out of this crisis of tradition, but he believes that before we can adopt these elements, we must clarify what childhood is. He therefore undertakes to do so, drawing on the philosophers who have identified or developed the aforementioned problem. As he tries to demonstrate, this exploration leads through the philosophy of language and aims at the concept of transcendental synesthesia that conditions and generates the images of childhood.